2020
DOI: 10.1108/bjm-04-2019-0119
|View full text |Cite
|
Sign up to set email alerts
|

The joint production of confidence – self-regulation in European crowdfunding markets

Abstract: PurposeThe paper discusses the rationale for a widespread reliance on Codes of Conduct (CoC) in European crowdfunding through the lenses of economic theories of self-regulation. By analysing the institutional design of CoCs in crowdfunding, the paper illustrates the differences in their regulatory context, inclusiveness, monitoring and enforcement. It offers the first systematic overview of substantial rules of CoCs in crowdfunding.Design/methodology/approachA comparative case study of nine CoCs in Europe is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Notably, as crowdfunding backers are often not able to judge the quality of platforms' services before their usage of the platform (Odorović and Wenzlaff, 2020), our data were collected mostly from backers who have contributed to crowdfunding campaigns before, where contribution was measured based on backer's total amount contributed over all campaigns in the past year. Observations with missing data or those suspected of monotonous response bias were removed from the dataset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, as crowdfunding backers are often not able to judge the quality of platforms' services before their usage of the platform (Odorović and Wenzlaff, 2020), our data were collected mostly from backers who have contributed to crowdfunding campaigns before, where contribution was measured based on backer's total amount contributed over all campaigns in the past year. Observations with missing data or those suspected of monotonous response bias were removed from the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier research by Hoegen et al (2018) confirmed that platform contextthat is, the affordances, general features and functionality of the platform (including which and how campaigns are visually presented to the potential investors)affects the flow of backers' contribution processes. Furthermore, evidence from various lenses including sustainability and cultural and arts sectors confirms that the choice of crowdfunding platform as funding technology by a fund-seeker is more complex (Maehle, 2020;Rykkja et al, 2020) and should not be based on intuitions (Baah-Peprah and Shneor, 2022) as these platforms ultimately influence behaviors (Odorovi c and Wenzlaff, 2020), such as backers' contribution behaviors on the platform (Ordanini et al, 2011). Also, other theoretical papers intuiting relationships between certain variables and crowdfunding acceptance lack empirical support and most have not been tested directly (Miglo, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2017). Institutional environments dictate the legal and ethical boundaries for the campaign content, financial formalities to be followed and legal protections (Odorović and Wenzlaff, 2020; Kshetri, 2015). Furthermore, fundraisers may enjoy and even need to meet with other stakeholders as part of the fundraising process.…”
Section: Engagementmentioning
confidence: 99%
“…Platforms have created self-regulation frameworks, which are designed to induce trust in domestic platforms and possibly to establish a market entry barrier for foreign platforms. However, even selfregulation documents as enshrined in codes of conduct and ethics adopted by various industry organization across Europe exhibit significant differences in terms of scope, ambition, and oversight (Odorović and Wenzlaff 2020).…”
Section: Regulation and European Crowdfunding Market Fragmentationmentioning
confidence: 99%